Green School Green School: Gerakan Penghijauan Sekolah Melalui Program Kebun Mini - Rahmawati, Vita; Fansuri Dwi Santoso, Faris; Fajariyah Haris, Rizkiyatul; Cyntia Pritasari, Ade; Dyah Puspitasari, Aditya (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
A clean and cool environment is every individual's dream. To create a clean environment, joint efforts are needed collectively. This service aims to explore the role of MBKM KKNT UTM 2024 students in implementing a mini garden work program in collaboration with SD Negeri Dasok 3, in order to create an environment that produces plants, such as fruit and vegetables, by utilizing unused land at the school. This program was initiated because the school conditions were quite barren; Even though they have large areas of land, this land has not been utilized optimally. In the PKM process held at SD Negeri Dasok 3, there are several stages, including preparation of a proposal, submission of permits to the authorities, the site observation stage is carried out to understand the situation and conditions of the field that will be used as the location for the mini garden. The results of this PKM show that the school greening movement through the mini garden program is going well and has received support from the school. However, based on the results of activities during the mini garden program, its implementation has not been completely successful due to several obstacles, namely: (1) arid soil conditions, (2) limited water in the dry season, (3) plant seed media that is not suitable for soil conditions , and (4) there are still students who do not care about this program. Overall, the school greening movement through the mini garden program has significant potential in creating a greener school environment, although it requires more effective strategies to overcome existing obstacles.